Factors Impacting Ticket Price Paid by Consumers on the Secondary Market for a Major Sporting Event - Nels Popp; Stephen Shapiro; Patrick Walsh; Chad McEvoy; Jason Simmons; Stephen Howell (Journal of Applied Sports Management, 2018)
In an era of dynamically priced tickets, sport marketers benefit from a greater understanding of factors impacting the price consumers are willing to pay. Past research has investigated external factors affecting ticket price on the secondary market, but little work has investigated internal factors and no prior research has utilized actual price paid as a dependent variable. The current study found age, income, prior attendance, timing of purchase, and seat location influenced secondary ticket price paid, explaining 44.9% of the variance, while fan identification and alumni status did not impact the amount patrons paid for tickets to a major college men’s basketball tournament. Subscribe to JASM
Keywords: dynamic pricing; ticket price; college basketball